Treatment Outcomes of Extensively Drug-Resistant Tuberculosis in Pakistan: A Countrywide Retrospective Record Review - Abubakar, Muhammad; Ahmad, Nafees; Ghafoor, Abdul; Latif, Abdullah; Ahmad, Izaz; Atif, Muhammad; Saleem, Fahad; Khan, Shereen; Khan, Amjad; Khan, Amer Hayat (Frontiers in Pharmacology, 2021)
Background The current study is conducted with the aim to the fill the gap of information regarding treatment outcomes and variables associated with unsuccessful outcome among XDR-TB patients from Pakistan. Methods A total of 404 culture confirmed XDR-TB patients who received treatment between 1st May 2010 and 30th June 2017 at 27 treatment centres all over Pakistan were retrospectively followed until their treatment outcomes were reported. A p-value <0.05 reflected a statistical significant association. Results The patients had a mean age 32.9+14.1 years. The overall treatment success rate was 40.6% (95% confidence interval [CI]:35.80-45.60%). A total of 155 (38.4%) patients were declared cured, 9 (2.2%) completed treatment, 149 (36.9%) died, 60 (14.9%) failed treatment and 31 (7.7%) were lost to follow up (LTFU). The results of the multivariate binary logistic regression analysis revealed that the patients’ age of >60 years (OR=4.69, 95%CI:1.57-15.57) and receiving high dose isoniazid (OR=2.36, 95%CI:1.14-4.85) had statistically significant positive association with death, whereas baseline body weight >40 kilograms (OR=0.43, 95%CI:0.25-0.73) and sputum culture conversion in the initial two months of treatment (OR=0.33, 95%CI:0.19-0.58) had statistically significant negative association with death. Moreover, male gender had statistically significant positive association (OR=1.92, 95%CI:1.04-3.54) with LTFU. Conclusion The treatment success rate (40.6%) of XDR-TB patients in Pakistan was poor. Providing special attention and enhanced clinical management to patients with identified risk factors for death and LTFU in the current cohort may improve the treatment outcomes